Perancangan Sistem Informasi Perpustakaan Berbasis Desktop Pada Kantor Pengadilan Agama Palopo - Hardiana Hardiana; Akramunisa Akramunisa (Department of Electrical Engineering, University of Patria Artha, 2022)
The Palopo Religious Court is one of the agencies located in the city of Palopo that is of a special judicial nature, which is authorized in certain types of islamic civil cases, only for people who are Muslims. The Palopo Religious Court, which is based on Jalan Andi Djemma Palopo, is one of the four judicial bodies of the first instance under the auspices of the Supreme Court of the Republic of Indonesia. However, based on the results of observations and interviews with one of the organizers, especially the library section of the Palopo Religious Court Office, there are still some problems with archiving books or libraries, namely the frequent duplication of data, data processing in this library is still carried out manually, the search for book layouts is very long so that it takes a long time and reports on the number of existing books and books borrowed in the library the office of the Palopo Religious Court is difficult to obtain, since the calculations are still manual. The purpose of this study was to produce a Desktop-Based Library Circulation Service Application at the Palopo Religious Court Office. The type of research used in this study is Research and Development research while the data collection method uses the observation and interview method approach. For system design using the Unified Modelling Languange (UML) approach version 3.1.9, Java Netbeans programming language version 8.2 and MySql data base 7.2.34. The process of managing circulation service data at the Palopo Religious Court office has not been computerized, which still uses conventional processes in the process. The library circulation service application has been tested using blackbox testing and from the test results it is concluded that all form and button displays have worked properly.